Indications of Genetic Admixture in the Transition Zone between Fagus sylvatica L. and Fagus sylvatica ssp. orientalis Greut. & Burd - Markus Müller; Precious Annie Lopez; Aristotelis C. Papageorgiou; Ioannis Tsiripidis; Oliver Gailing (Diversity, 2019)
Two subspecies of European beech (Fagus sylvatica L.) can be found in southeast Europe: Fagus sylvatica ssp. sylvatica L. and Fagus sylvatica ssp. orientalis (Lipsky) Greut. & Burd. (Fagus orientalis Lipsky). In a previous study, based on genetic diversity patterns and morphological characters, indications of hybridization between both subspecies were found in northeastern Greece, a known contact zone of F. sylvatica and F. orientalis. Nevertheless, potential genetic admixture has not been investigated systematically before. Here, we investigated genetic diversity and genetic structure of 14 beech populations originating from Greece and Turkey as well as of two reference F. sylvatica populations from Germany based on nine expressed sequence tag-simple sequence repeat (EST-SSR) markers. Very low genetic differentiation was detected among F. sylvatica populations (mean GST: 0.005) as well as among F. orientalis populations (mean GST: 0.008), but substantial differentiation was detected between populations of the two subspecies (mean GST: 0.122). Indications for hybridization between both subspecies were revealed for one population in Greece. One of the genetic markers showed specific allele frequencies for F. sylvatica and F. orientalis and may be used as a diagnostic marker in future studies to discriminate both subspecies.